Isolated tubercular abscess in immunocompetent children: A systematic review of case reports - Rajkumar Kundavaram; Sourabh Singh; Amber Kumar; Shikha Malik; Girish Chandra Bhatt (Wolters Kluwer Medknow Publications, 2023)
Background: Tuberculosis (TB) is a common disease, especially in low-income countries, with a varied clinical spectrum involving multiple organs. Although liver abscess can be seen in 70% of patients with miliary tuberculosis, isolated tuberculous liver abscess (ILTA) is rare in immunocompetent children. Liver involvement, though seen in up to 70% of patients as a part of miliary TB, isolated tuberculous liver abscess (ITLA) is rare in 13 children. Objective: The present systematic review focuses on demographic parameters, clinical presentations, duration of antitubercular treatment, and the need for surgical intervention and recurrence in children with tuberculous liver abscess. Methods: A comprehensive search was done in major databases PubMed and Google Scholar using defined search terms encompassing case reports or case series on isolated tubercular liver abscess in children. The identified reports underwent screening by three different authors for inclusion and exclusion criteria. Results: The median (interquartile range [IQR]) age of presentation was 9.5 (6.5) years, with a slightly higher prevalence in females (59%). The most common presenting symptom was fever (95%), followed by abdominal pain (68%). Hepatomegaly was seen in 90% of cases and jaundice in 16%. The median (IQR) duration of antitubercular treatment was 6 (4) months and surgical intervention was required for 14 (63%) children. The resolution time of the ITLA varied across the children, with a median (IQR) time being 2 (7) months. Conclusion: Pediatric tubercular liver abscess requires a high index of suspicion, particularly in endemic countries like India. Children with liver abscess should be evaluated for TB, if response to initial management is poor. Early diagnosis and prompt treatment with systemic antitubercular treatment are associated with a favorable outcome.